Long-Term Impact of Social Isolation and Molecular Underpinnings - Arzate-Mejía, Rodrigo G.; Lottenbach, Zuzanna; Schindler, Vincent; Jawaid, Ali; Mansuy, Isabelle M. (Frontiers in Genetics, 2020)
Prolonged periods of social isolation can have major detrimental effects on the physiology and behavior of social animals, however, their underlying molecular mechanisms remain unclear. In this review, we provide a comprehensive overview of the acute and lasting effects of prolonged periods of social isolation with a focus on the molecular events leading to behavioral alterations. We highlight the increasingly recognized role of epigenetic mechanisms and non-coding RNA in the control of gene expression as a response to social isolation and provide a cautionary tale on the indiscriminate implementation of strict quarantines during epidemics that might lead to prolonged periods of social isolation, and potentially, detrimental and lasting effects in metal health.